KERJASAMA PADA SISTEM EKONOMI SYARIAH (Analisis atas Pembiayaan Akad Mudharabah) - Apipudin Apipudin (Jurnal Ilmiah Ekonomi Bisnis, 2015)
The study aims at observing analitically of Mudharabah Contract Finance on islamic economy system. The study uses descriptive qualitative analysis with historic-juridical approach. The data collecting technique in the study is based on literature such as book, journal, and other scientific works which is  either related or unrelated with the study. The result of analysis ndicates that multilateral mudharabah contract finance is based on MUI and National Islamic Law Committee instruction with mortgage (al-Rahn) analogy (al-Qias)-based argument. The National Islamic Law Committee instruction is cross with the classical scientists who does not determine the mudharabah contract finance for either bilateral or multilateral.  Keywords: Musyarakah, Mudharabah, Mudharabah musyarakah